Interpolative construction for operator ideals - Reﬁce, Nawal (Faculty of Mathematics and computer sciences Department of Mathematics - Option : Functional analysis, 2020)
In this memory we study the interpolations method presented by Jarchow and Matter in ordre to get a new scale of operators ideal, as (p,σ)-absolutely continuous operators. Domination and factorisation theorems of Piesch about this class are presented.
Keywords: Linear operator ideals, p-summing operators,Piesch domination and factoriza tion theorems ,(p,σ)-absolutely continuous operators .